2009
DOI: 10.1111/j.1365-2672.2008.04026.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of fluoroquinolone antimicrobial agents by anEscherichia colistrain isolated from a municipal wastewater treatment plant

Abstract: Aims:  To isolate environmental bacteria capable of transforming fluoroquinolones to inactive molecules. Methods and Results:  Bacteria were isolated from the aerobic liquor of a wastewater treatment plant on a medium containing norfloxacin (100 mg l−1). Twenty‐two isolates were highly resistant (minimal inhibitory concentration: 6·25−200 μg ml−1) to five fluoroquinolones and six of them were positive by PCR amplification for the aminoglycoside resistance gene aac(6′)‐Ib. Of these, only Escherichia coli strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 61 publications
1
31
0
4
Order By: Relevance
“…qnrS2 was found on a plasmid isolated from the activated sludge basin of a wastewater treatment plant in Germany at about the same time (14,99). qnrS from veterinary clinical E. coli isolates in Guangdong, China, that was deposited in GenBank as qnrS1 (GenBank accession number ABU52984) differed from qnrS1 in one codon and has thus been renamed qnrS3.…”
Section: Discovery Of Qnr Genesmentioning
confidence: 99%
“…qnrS2 was found on a plasmid isolated from the activated sludge basin of a wastewater treatment plant in Germany at about the same time (14,99). qnrS from veterinary clinical E. coli isolates in Guangdong, China, that was deposited in GenBank as qnrS1 (GenBank accession number ABU52984) differed from qnrS1 in one codon and has thus been renamed qnrS3.…”
Section: Discovery Of Qnr Genesmentioning
confidence: 99%
“…Pure cultures of bacteria and mixed cultures from wastewater treatment plants degrade the piperazine moieties of some fluoroquinolones (1, 12, 13). A modified aminoglycoside acetyltransferase from Escherichia coli is responsible for acetylation of fluoroquinolones (28,43).It seemed possible that bacteria capable of fluoroquinolone modification or degradation could be isolated from a wastewater treatment plant and that the metabolites produced could be identified to determine the metabolic pathways. By using HPLC, mass spectrometric (liquid chromatography-ESI-MS/MS [LC-ESI-MS/MS]), and proton nuclear magnetic resonance (NMR) analyses, it was shown that a norfloxacin-insensitive strain of Microbacterium sp.…”
mentioning
confidence: 99%
“…Production of N-acetylnorfloxacin and N-nitrosonorfloxacin by environmental Mycobacterium sp. strains has also been found, but the enzymes responsible for modifications are unknown (15) and the aac(6=)-Ib-cr variant gene has not been detected in these strains (12).…”
mentioning
confidence: 99%
“…In some strains of Escherichia coli, a mutated aminoglycoside acetyltransferase, AAC(6=)-Ib-cr, acetylates fluoroquinolones at the N-terminal of the piperazine ring (12)(13)(14) and enhances bacterial resistance to these drugs (14). Production of N-acetylnorfloxacin and N-nitrosonorfloxacin by environmental Mycobacterium sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation